Review on advances in thermoelectric conversion using ion-conducting polymers. (15th June 2021) - Lei, Bowen; Bai, Shuxin; Ju, Su; Yin, Changping; Chen, Chen; Zhang, Jianwei
Abstract: The ionic Seebeck effect has been extensively investigated in thermoelectric conversion due to the substantial Seebeck coefficient it promotes. In this context, polymer-based electrolytes have been reported as one of the good ionic Seebeck material categories, demonstrating extraordinary potentials in heat collection for wearable and adaptable hardware. In this review, we make a summary of the latest progress in the ponder for ionic thermoelectric systems based on organic polymer electrolytes and mixed ionic-electronic conductors. Moreover, the investigation on the electrodes utilise in ionic thermoelectric devices is discussed. Finally, the recent progress in novel applications of ionic thermoelectric systems, including ionic thermoelectric supercapacitors, transistors, and sensors, which utilise the materials mentioned above' aggregate vital properties, is also discussed.